Albert Watkins in Selma, CA - Watkins, Howard::::::::: (1978)
Gregory Knoll from Legal Aid Society of San Diego; Speaker ? Albert Watkins at intersection of E. Front and Center Streets, Selma CA; in background Libby, McNeil water tower